The main consequences of solid waste on the environment and the health of the population in the municipality of Cabaret-Haiti - Charles, Ralph; de Oliveira, Regina Célia; Spanghero, Pedro (Revista Geográfica de América Central., 2018)
Solid waste management for a more sustainable world is always present at world conferences on the environment, and is a strategy to reconcile development with protection of ecosystems, considering that the generation and final disposal of urban solid waste is now a days a of the major problems of modern society. One of the reflexes of this neglect is easily perceived among the population, as in the case of the lack of basic sanitation, which damages beyond the environment itself, human health with contamination of soil, bodies of water, food and quality of the air, implying in numerous cases of diseases. These residues can be financial sources, and can be reused for other purposes, at the same time, can be considered as a danger to the sustainability of the planet. Thus, this article aims to present scenarios of events that have caused environmental changes in the dynamics of land use in Cabaret-Haiti, mainly through the perception of the population on the management of solid waste and the improper disposal of garbage, aiming at preserving and restoring the environmental quality conducive to life.